Variations in the aortic - common iliac bifurcation in man - a cadaveric study - Maneesha Sharma; Tripta Sharma; Richhpal Singh (Wolters Kluwer Medknow Publications, 2013)
Background and aims: The abdominal aorta usually terminates at the level of L4 vertebral body into common iliac arteries. With the present day advancements in vascular surgery and neurological surgeries involving approach to lumbar vertebral bodies, we need to know any variations from this normal course. So, the present study aimed at knowing the anatomical variations in the termination of abdominal aorta and in common iliac arteries which might prove to be of some help in some of such surgeries. Material and methods: The study was conducted on 35 adult (29 males and 6 females) embalmed cadavers obtained from anatomy departments of Govt. Medical college, Amritsar and Gian Sagar Medical college, Ramnagar, Punjab. The abdominal cavity was opened, peritoneum stripped off from aorta at its bifurcation, variations in its termination, common iliac arteries and their branches were carefully observed and recorded. Results: In 54.29% cases the level of aortic bifurcation was found opposite 4th Lumbar vertebra, in the rest it was variable between L3 and L5 vertebra. Conclusions: These variations may lead to some trouble during vertebral surgeries, making it essential to investigate and locate the exact position of great vessels before the commencement of surgery.